Testing the acceptability and feasibility of video observational methodology to measure parent-adolescent communication and interaction - Lekhuleni, Fortunate; Desai, Rachana; Coetzee, Bronwyne; Pearson, Rebecca; Rochat, Tamsen Jean (Frontiers in Child and Adolescent Psychiatry, 2023)
Background Existing research has shown that the parent-adolescent relationship and its associated communication and interaction styles are important for adolescent development and outcomes. Measuring parent-adolescent communication and interaction using self-report methods has substantial research limitations. Video observational methodologies offer a novel and more objective approach to measuring parent-adolescent communication and interaction from the point of view of participants. This study aims to explore the feasibility and acceptability of this methodology, and analysis using automated coding software in an urbanized context. Methods This study recruited parent-adolescent pairs in Soweto, South Africa which included 11–15-year-old adolescents and their biological parents. Parent-adolescent communication and interactions were measured using novel video observational portable head cameras called “Teencams”. Feasibility was evaluated by testing three observational game tasks (Matching pairs card game, Jenga and Charades) to stimulate communication and interaction between 16 parent-adolescent pairs, and the Teencam's ability to record video and audio content. Acceptability was explored using one-on-one interviews with the parents (n = 14), on whether they found the Teencam comfortable to wear, whether the parents believed their adolescents acted naturally, and which observational game tasks were feasible during their interactions. The videos were analysed using automated coding software called FaceReader which detects and codes basic facial expressions. Results The Teencam methodology was found to be feasible and acceptable amongst parent-adolescent pairs in Soweto, South Africa. The Matching pairs card game stimulated excellent interaction and communication with good video and audio quality. Some feasibility limitations were identified in the operations (switching on/off and starting recording), the ability of the device to cope with the movement of the participants, and the lighting conditions of the room, all of which resulted in poor coding and analytic output from FaceReader. Refinements and adjustments were made to the methodological protocol by improving the head cameras and lighting conditions and refining the Matching pairs card game, which resulted in improved analytic output from FaceReader. Conclusion Based on these findings, a methodological protocol was developed to measure parent-adolescent interaction and communication in an urban setting. The unique contribution of this research lies in its potential to lead to improved methodologies for measuring parent-adolescent communication and interactions.